Simultaneous Electrochemical Removal of Selenium and Strontium from Aqueous Solution - Katarina Licht; Ivan Halkijević; Hana Posavčić; Domagoj Nakić (Applied Sciences, 2025)
This study investigated the removal of selenium (Se) and strontium (Sr) from water using a three-stage electrochemical reactor with integrated pH control. A total of 102 experiments were performed following a Box–Behnken design that varied the electrode material, applied current, number of electrodes, operating time, and initial pH to evaluate their effects on the Se and Sr removal efficiencies. The complete removal of Se was achieved under multiple conditions, even without pH control, while effective Sr removal required a high current and initial pH adjustment. The top performance for both elements was achieved with a 25 A current, four Fe electrodes, 15 min of operational time per phase (cycle), and a middle range of pH values, which resulted in 97.92% and 99.96% removals of Sr and Se, respectively. This research highlighted the novel approach of using electrochemical pH control to achieve high removal efficiencies of Se and Sr from water in a short operating time, which surpassed the efficiencies reported in previous studies.